Analisis Keragaan Karakter Morfologi Delapan Aksesi Bawang Merah (Allium ascalonicum L.) Pada Lahan Sawah di Kabupaten Karawang - Maesaroh, Dita; Azizah, Elia; Agustini, Rika Yayu (Faculty of Agriculture Universitas Singaperbangsa Karawang, 2023)
Shallots (Allium ascalonicum L.) is a crucial vegetable commodity because it has a high nutritional content and the demand for shallots in Indonesia is increasing. Efforts to meet the demand for shallots in Indonesia are the use of high yielding varieties in order to spur increased productivity of shallots in the lowlands. This study aims to obtain the best results from the analysis of the morphological character of eight red onion accessions in rice fields in Karawang district. The research was carried out in the experimental field of the Faculty of Agriculture, Singaperbangsa Karawang University, which is located in Pasirjengkol Village, Majalaya District, Karawang Regency. The research method used a single factor Randomized Block Design (RAK). There were 8 treatments and repeated 4 times, so there were 32 experimental plots. Data were analyzed using analysis of variance and further test with DMRT (Duncan Multiple Range Test) at 5% level. The results of this experiment showed that there was a significant effect of the appearance of the morphological characters of shallot accessions on the growth components (plant height, number of leaves, and number of bulbs). The BM5 (Bima) treatment gave the best results on plant height of 33.25/cm, and BR6 (Berlind) treatment gave the best results on the number of leaves of 42.40/strand, and the number of tubers of 16.50/ clove.